2002
DOI: 10.1034/j.1600-0609.2002.02771.x
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of CA 125 in patients with non‐Hodgkin's lymphoma

Abstract: Measurement of serum CA 125 is useful for staging, monitoring, and estimating prognosis in patients with NHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 35 publications
1
35
0
4
Order By: Relevance
“…High levels are observed in other conditions such as lung cancer, gastrointestinal cancer, abdominal military tuberculosis, endometriosis, and pelvic inflammatory disease [10,[1][2][3]. CA-125 has been also found to be significantly elevated in patients with chronic congestive heart failure (HF) [4][5][6][7]11]. Idalou et al [6] had previously shown that CA-125 level was correlated with deceleration time, right atrial pressure, SPAP and pulmonary artery wedge pressure.…”
Section: Discussionmentioning
confidence: 99%
“…High levels are observed in other conditions such as lung cancer, gastrointestinal cancer, abdominal military tuberculosis, endometriosis, and pelvic inflammatory disease [10,[1][2][3]. CA-125 has been also found to be significantly elevated in patients with chronic congestive heart failure (HF) [4][5][6][7]11]. Idalou et al [6] had previously shown that CA-125 level was correlated with deceleration time, right atrial pressure, SPAP and pulmonary artery wedge pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [26] have tested and reported the sensitivity of these markers about predicting lymphoma, LDH (20.83%), b 2 -MG (57.29%) and CA125 (47.90%), respectively. It was early reported the total positive ratio of LDH and CA125 were only 38% [35] and 40-50% [36], respectively. While many markers have been developed and none of them were recognised as highly sensitive and specific gold standard marker [37].…”
Section: Discussionmentioning
confidence: 99%
“…The ranges of PLR and negative likelihood ratio were 2.99-96.09 and 0.04-0. 35 For potential additional quality items, diagnosis was established using path morphological or other evidence to confirm. And the technology of the index test was SELDI-TOF-MS. Because SELDI is a very extremely sensitive technique and many factors can impact its repeatability, the parameters of instrument were very important for experiment result.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly elevated LDH often appeared in non-infectious diseases such as tumor, because increased LDH reflected metastasis and highly degree of malignant tumor. 12 Blood etc. which were related with tumor tissue contained increased LDH.…”
Section: Discussionmentioning
confidence: 99%